Fulminant Guillain–Barré syndrome with Takotsubo cardiomyopathy: Report of an autopsied case. Issue 4 (25th June 2018) - Takemoto, Mami; Yamashita, Toru; Ohta, Yasuyuki; Hishikawa, Nozomi; Sato, Kota; Tsunoda, Keiichiro; Shang, Jingwei; Deguchi, Kentaro; Tanaka, Takehiro; Nishimura, Hirotake; Furutani, Masumi; Abe, Koji
Abstract: We report a case of a 77‐year‐old Japanese man with a fever of up to 39.0°C, which subsided after 5 days. The patient showed fulminant Guillain–Barré syndrome (GBS), severe autonomic dysfunction with a labile blood pressure, an unstable heart rate from onset to death, and Takotsubo cardiomyopathy. Although Takotsubo cardiomyopathy was ameliorated by Day 14 (from admission in the hospital) with a normalized electrocardiogram, his blood pressure became markedly more variable and he died on Day 26. In the present report, we describe an autopsied case of GBS with Takotsubo cardiomyopathy.